The Impact of Interest Rates on the Real Estate Market - Mo, Jieling (2009)
This paper investigates the impact of interest rate on real estate market. It estimates the impact of interest rates upon house price movements from 1980 to 2008 across 16 countries. I employ static panel data model to estimate determinants of house prices using a across country panel dataset. I also take a novel analysis for the fundamental determinants of house prices. The results show that unemployment rate, the share of active population, real broad money, short-term interest rate and inflation rate are negatively associated with house prices, and real per capita GDP is positively correlated to house prices. In particular, the short-term interest rate elasticity of house prices is -13.75. This result indicates that short-term interest rates play very important role in house prices and hence have a large impact on real estate market.